The correct answer is option B which is -4.(-3)5x.
Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division
The expression will be solved as:-
E = ( 4 - ( -3 )) 5x
E = 4 (+3) ( 5x)
E = 12(5x)
E = 60x
Now we will check option B
E1 = -4(-3)5x
E1 = 12 (5x)
E1 = 60x
E = E1
Therefore the correct answer is option B which is -4.(-3)5x.
To know more about Expression follow
https://brainly.com/question/723406
#SPJ1